2022
DOI: 10.3390/plants11233223
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Long Non-Coding RNA (lncRNA) in Response to Seed Aging in Rice

Abstract: Many lncRNAs have been shown to play a vital role in aging processes. However, how lncRNAs regulate seed aging remains unknown. In this study, we performed whole transcriptome strand-specific RNA sequencing of samples from rice embryos, analyzed the differences in expression of rice seed lncRNAs before and after artificial aging treatment (AAT), and systematically screened 6002 rice lncRNAs. During the AAT period, the expression levels of most lncRNAs (454) were downregulated and only four were upregulated amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…A genomic view of lncRNAs in rice seed revealed that lncRNAs undergo extensive alternative splicing during the transition from milk seed to mature embryo and endosperm, and lncRNAs could maintain more exons in embryos [57]. Alternative splicing forms of a rice lncRNA LNC_037529 were also identified in artificial aging seed [58]. These results suggest that the alternative splicing of lncRNA is widely present in metabolic processes.…”
Section: Seed Dormancy and Seed Longevitymentioning
confidence: 90%
“…A genomic view of lncRNAs in rice seed revealed that lncRNAs undergo extensive alternative splicing during the transition from milk seed to mature embryo and endosperm, and lncRNAs could maintain more exons in embryos [57]. Alternative splicing forms of a rice lncRNA LNC_037529 were also identified in artificial aging seed [58]. These results suggest that the alternative splicing of lncRNA is widely present in metabolic processes.…”
Section: Seed Dormancy and Seed Longevitymentioning
confidence: 90%
“…LncRNAs participate in important age-related signaling pathways via regulation the expression of target genes in cis or trans modes 20 . A large number of differentially expressed lncRNAs were identified, which target genes were coding proteins involved in age-related signaling pathways, like enzymes associated with cell wall degradation, lipid peroxidation, and secondary metabolism 21 . Some DE-lncRNAs, such as lncRNAs MSTRG.31014.21 and MSTRG.31014.36, which are possibly involved in flag leaf senescence of rice could regulate the abscisic-acid biosynthetic gene BGIOSGA025169 (OsNCED4) and BGIOSGA016313 (NAC family) 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al identified that the transcription factor bZIP23 bound to the genetic factor PER1A of peroxidase in rice through metabolome and transcriptome technologies, and was involved in the clearance of reactive oxygen species during seed aging [11]. Zhang et al performed strand-specific RNA sequencing on rice embryonics of fresh-dried seeds (96% germination percentage) and aged seed samples (50% germination percentage; aged for 6 days at 43 • C and 85% relative humidity) and detected four upregulated lncRNAs that predominantly regulated target genes involved in base repair, either in cis or trans -regulated target genes [12]. Gu et al conducted an integrated analysis of proteomics and genomics on 20 different rapeseed varieties with varying oil contents, identifying 165 differentially expressed proteins (DEPs), and 31 unique genes showed significant differences in the germination process between high-and low-oil-content seeds, with 13 of these genes potentially being related to seed germination vigor [13].…”
Section: Introductionmentioning
confidence: 99%